REPRESENTASI FEMINISME EKSISTENSIAL DALAM FILM AMBU KARYA FARID DERMAWAN - Tita Putria; Fajar Sukma Nur Alam (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2025)
This study aims to analyze the representation of existentialist feminism in the film Ambu directed by Farid Dermawan, using Simone de Beauvoir’s existentialist feminism theory and Tzvetan Todorov’s narrative structure theory. Ambu was chosen because it portrays the conflict between women and customary traditions in the Baduy community, focusing on the struggle of the main character, Fatma, in defining her own existence. This research employs a descriptive qualitative method with content analysis techniques based on visual and verbal narratives in the film. The findings show that Fatma is positioned as the Other, yet she actively rejects this position through free and conscious actions. She is portrayed as an independent woman, owning a catering business, thinking critically, and taking full responsibility for her daughter's future even when gravely ill. The three key concepts in existentialist feminism the Other, freedom, and transcendence are clearly reflected in Fatma’s life journey. Additionally, the narrative structure of the film follows Todorov’s five-stage model, starting from initial equilibrium to a new balance achieved after conflict and reconciliation between mother and daughter. This study concludes that Ambu successfully represents the struggle of women to become free and responsible subjects amidst social and cultural pressure.